Upheaval buckling of pipelines due to internal pressure: A geometrically nonlinear finite element analysis. (1st March 2018) - Craveiro, Marina Vendl; Gay Neto, Alfredo
Highlights: A geometrically nonlinear FE analysis of upheaval buckling of pipelines is presented. The only triggering for buckling is the internal pressure of the fluids transported. Discussions about how to apply the internal pressure load are made. The interaction between the pipe and the soil is represented by a contact model. The relative influence of soil imperfections and friction in buckling is discussed. Abstract: This work presents an analysis of upheaval buckling of pipelines triggered by internal pressure. It discusses the existing relationship between internal pressure and equivalent compressive axial force in the buckling context. The main focus is on the relative influence of prop imperfections and soil friction coefficients in critical load prediction and post-buckling configuration. To perform the analyses, numerical models are developed using geometrically-exact finite element of beams, undergoing large displacements and finite rotations. Contact between the pipeline and the soil is also included in the models. As a result, the work shows the equivalence of applying the internal pressure as a distributed load dependent on pipe curvature and as a follower compressive axial force, both in terms of critical load and post-buckling configuration. Varying prop imperfections and soil friction coefficients, it is concluded that the first parameter has more influence in critical load prediction than the last one. The same occurs in terms of post-buckling configuration: for the same increase of internal pressure from critical load, the imperfections have more influence in the post-buckling displacements than the friction between the pipeline and the soil.